Pharmacological inhibition of acetylcholine-regulated potassium current (IK, ACh) and associated A1- and M2-pathways prevent atrial arrhythmogenic changes in a rat model for obstructive sleep apnea. (25th November 2020) - Linz, B; Hauge Thostrup, A; Saljic, A; Rombouts, K; Wirth, K; Hohl, M; Linz, D; Jespersen, T
Abstract: Background: In obstructive sleep apnea (OSA), intermittent hypoxemia and intrathoracic pressure fluctuations may increase vagal tone and adenosine release, potentially resulting in an increased acetylcholine-regulated potassium current (IK, ACh). Here we elucidated acute atrial electrophysiological effects of obstructive respiratory events simulated by intermittent negative upper airway pressure (INAP) and the role of atrial IKACh activation by A1-receptor and M2-receptor activation. Methods: In sedated spontaneously breathing rats (2% isoflurane), either IK, ACh-inhibitor (XAF-1407: 1mg/kg), M2-receptor inhibitor (atropine; 1μg/kg), A1-receptor inhibitor (Rolofylline; 1μg/kg) or a buffer-based vehicle was perfused (Control). INAP was applied non-invasively by a negative pressure device 14 times throughout 70 minutes. Simulated apneas were maintained for one minute with a four minute resting period. Atrial effective refractory period (AERP) and atrial activation time were acquired by a programmed atrial pacing protocol before, during and after applied INAP throughout the study. Results: Independent of IK, Ach-inhibition, single INAP applications prolonged transiently atrial activation times (Control: INAP vs. pre-INAP p=0.034; XAF-1407: INAP vs. pre-INAP p=0.039). In control-rats, seventy minutes of repetitive INAP decreased AERP by 15.45±0.06% (vs. baseline p=0.0015), which was reversible upon 1 hour of recovery. AERP shortening correlated with the cumulative pressure applied per body weight (Pearson r=−0.773; p=0.025). Whilst only XAF-1407 and atropine increased baseline AERP, all drug interventions, XAF-1407, atropine and Rolofylline could prevent INAP-associated AERP shortening (end INAP-protocol vs. respective baseline XAF-1407 p=0.994; atropine p=0.984; Rolofylline p=0.951). Drops in oxygen saturation and applied INAP were comparable in all groups. Conclusion: Short-term simulated OSA is associated with progressive AERP shortening, which was determined by the cumulative negative airway pressure applied. This potentially represents an important insight in future OSA treatment. Pharmacological IK, ACh inhibition prevented INAP-associated AERP-shortening suggesting an involvement in acute atrial arrhythmogenesis in OSA. However, if IK, Ach and its potential upstream activating A1- and M2-pathway pose a pharmacological treatment target for OSA-patients with AF, requires further investigation. Funding Acknowledgement: Type of funding source: None